2020
DOI: 10.1016/j.langsci.2019.101268
|View full text |Cite
|
Sign up to set email alerts
|

Twitter trolls: a linguistic profile of anti-democratic discourse

Abstract: This article focuses on anti-democratic discourse and investigates the linguistic profile of Twitter trolls. The troll data consist of some 3.5 million messages in English obtained through Twitter in late 2018. These data originate from potentially state-backed information operations aimed at sowing discord in Western societies. The baseline data, against which the troll data are compared, contain circa 4.4 million messages in English drawn from the Nordic Tweet Stream corpus. A machine learning application th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…More importantly, it is clear that as long as we choose different baseline datasets, we will most likely get different results. Thus, in stark contrast to what Zannettou et al discovered, Lundberg and Laitinen in [16] argued that the troll messages are shorter than their baseline material and resemble more formal registers in that they contain a higher proportion of nouns. As we will see below, the latter observation is more compatible with our own results than the former.…”
Section: Introductionmentioning
confidence: 73%
“…More importantly, it is clear that as long as we choose different baseline datasets, we will most likely get different results. Thus, in stark contrast to what Zannettou et al discovered, Lundberg and Laitinen in [16] argued that the troll messages are shorter than their baseline material and resemble more formal registers in that they contain a higher proportion of nouns. As we will see below, the latter observation is more compatible with our own results than the former.…”
Section: Introductionmentioning
confidence: 73%
“…Because political trolling is widespread on the platform, recent scholarly attention was given to the automatic identification of online trolling on Twitter through linguistic analysis of trolling datasets [e.g., 5,20,21,22,23]. Efforts to identify trolling on Twitter are important, as these trolls negatively affect the political process, cause distrust in the political systems, and increase political polarization and conflict [24].…”
Section: Relevant Workmentioning
confidence: 99%
“…The "Kremlin trolls" simply aim to undermine American political institutions, spread discord within American society, and undermine the United States' global influence [25]. Scholars [23] focused on anti-democratic discourse and investigated the linguistic profile of Twitter trolls and found that trolls tend to write shorter posts and used a smaller number of lexical types and tokens. Others [22] developed machine learning models that predict whether a Twitter account is a Russian troll, using both behavioral and linguistic features.…”
Section: Relevant Workmentioning
confidence: 99%
“…Troll messages are "powerful weapon in modern hybrid warfare" (Monakhov, 2020, p. 2). For state-backed anti-democratic agents seeking to shift power dynamics, language can be a crucial resource for the strategic amplification of messages (Lundberg & Laitinen, 2020). Topics and sentiments that accompany words operate simultaneously in a message.…”
Section: Disinformation Campaign and Audience Engagementmentioning
confidence: 99%